Significance of lncRNA abundance to function - Grammatikakis, Ioannis; Lal, Ashish (Mammalian genome, 2022)
Long noncoding RNAs (lncRNAs) have emerged as regulators of diverse cellular processes. Although the vast majority of lncRNAs are expressed at lower levels compared to messenger RNAs (mRNAs), many lncRNAs play a central role in the regulation of cellular homeostasis and gene expression. With the advancement of next generation sequencing technologies, recent studies illustrate the diversity of lncRNA function. This diversity can be due to differences in their mechanisms of action, spatio-temporal expression, and/or abundance, all of which can vary depending on the particular cell type or tissue. Here, we discuss how the abundance of lncRNAs is an important feature that is often linked to their functions, and why it is crucial to quantitate lncRNA abundance, its local concentration within a cell or a tissue or the dynamic changes in expression levels during cell cycle progression or upon environmental stimuli, to shed light on their physiological roles.